(untitled) (Itinera, 2017)
Enlighted by Martha Nussbaum in an influential monograph (From Disgust to Humanity, 2010), the category of disgust towards the homosexuals provides a productive theoretical frame of reference for a re-reading of the Italian cultural politics between the 19th and the 20th Century. Furthermore, among its contemporary narrative accounts we may read two strands of the fictional representation of the homophobic disgust: a provocative one, aiming at narrating the transformations affecting the Italian social structures of the Seventies and of the Eighties (Natalia Ginzburg, Pier Vittorio Tondelli), and an internalized one, reflecting, often autobiographically, the crisis of the homosexual person/artist (Pier Paolo Pasolini, Walter Siti).Â